Climate Action and Global Health Dynamics for Thriving Global Communities: A Bibliometric Analysis - Okore, Lavender Awino; Maina, Purity Watetu; Molnár, Edina (Acta Carolus Robertus, 2025)
The study aimed to review the evolution of scholarship on climate action and global health dynamics over the years. We identified trends, clusters and potential gaps in research at the nexus of climate change and health. Further, the study analyses co-occurrence, trend topics, thematic analysis, citation and geographic affiliations. The analysis was carried out as per the PRISMA Guidelines, using the PRISMA Statement 2020. We retrieved 500 peer-reviewed papers based on keywords search and exclusion criteria on the Scopus and Web of Science Databases. To inform evidence-based policymaking, our study highlights evolving themes, potential study gaps, geographic distribution, research clusters, trend topics and existing author collaborations. The core purpose of conducting the bibliometric analysis is to advance the curation of empirical and theoretical-based strategies for mitigating the adverse global effects of climate change on global health. Additionally, by bringing forth the gaps, the study informs the design of climate action and health interventions towards addressing the 21st Century challenges in human health.
Keywords: climate change; climate action; global health